2008
DOI: 10.1007/s00284-008-9254-1
|View full text |Cite
|
Sign up to set email alerts
|

High-Level Expression in Escherichia coli, Purification and Mosquito-Larvicidal Activity of the Binary Toxin from Bacillus sphaericus

Abstract: The mosquito-larvicidal binary toxin produced by Bacillus sphaericus consists of two polypeptides: BinA and BinB. Both proteins function together, and maximum toxicity is obtained when both are present in equimolar ratio. Cloning and expression of each component separately in heterologous hosts led to low toxicity of the crystal proteins. To improve the expression level, the purification process, and the activity of the binary toxin, the binA and binB genes were separately cloned in Escherichia coli. Each gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Various reports have earlier described cloning and expression of one or both of the bin genes in different hosts, like in B. subtilis (Baumann and Baumann, 1989), in B. thuringiensis subsp. israelensis (Bourgouin et al, 1990) and in E. coli (Baumann et al, 1985Davidson et al, 1990;Ahmad et al, 1998;Promdonkoy et al, 2003Promdonkoy et al, , 2008. In most of these experiments, the binary toxins expressed as inclusion bodies and the toxicity was assayed by feeding either cells or total cellular proteins from these cells.…”
Section: Introductionmentioning
confidence: 99%
“…Various reports have earlier described cloning and expression of one or both of the bin genes in different hosts, like in B. subtilis (Baumann and Baumann, 1989), in B. thuringiensis subsp. israelensis (Bourgouin et al, 1990) and in E. coli (Baumann et al, 1985Davidson et al, 1990;Ahmad et al, 1998;Promdonkoy et al, 2003Promdonkoy et al, , 2008. In most of these experiments, the binary toxins expressed as inclusion bodies and the toxicity was assayed by feeding either cells or total cellular proteins from these cells.…”
Section: Introductionmentioning
confidence: 99%
“…AJ224478). Escherichia coli strain JM109 was used as a host strain to express the GST-BinA and GST-BinB proteins from pGEX-BinA and pGEX-BinB, respectively (21). The recombinant plasmid pGEX-BinA encoding the GST-BinA fusion protein was used as a template for mutagenesis.…”
Section: Bacterial Strains and Oligonucleotidesmentioning
confidence: 99%
“…Larvicidal activity assays were performed against 2nd-instar Culex quinquefasciatus larvae as described previously (Promdonkoy et al, 2008). BinA and BinB inclusions were mixed at 1:1 molar ratio and the concentration of total protein was adjusted to 50 lg/ml.…”
Section: Mosquito-larvicidal Activity Assaysmentioning
confidence: 99%
“…BinA is degraded into three fragments, with proteolytic cleavage sites identified at Met-103 and Arg-207 (Promdonkoy et al, 2008). It has been demonstrated that the BinA C-terminal half, from Met-208 to Phe-353, is responsible for interaction with BinB (Limpanawat et al, 2009).…”
Section: Introductionmentioning
confidence: 99%